Curing and Thermal Properties of Epoxy Resin Containing Nanosilica Particles - Parashar, Vijay; Kukreja, Parveen; Narula, A.K. (Asian Journal of Chemistry, 2010)
This paper describes the synthesis and curing behaviour of nanosilica particles and to study the modification in flammable properties of epoxy resin. Nanosilica particles were synthesized by using tetraethoxysilane (TEOS). Surface morphology was studied by SEM technique and particle size analysis was done by TEM studies. The size of nanosilica particles was in the range of 100 nm. The effect of nanosilica particles on the curing kinetics of epoxy resin along with 4,4'-diphenyldiamino sulphone (DDS) was studied by differential scanning calorimetry. Differential scanning calorimetry scans were recorded using TA 2100 thermal analyzer having 910 DSC module. The curing of diglycidyl ether of bisphenol-A (DGEBA) was initiated at higher temperature with DDS alone as compared to that with a mixture of nanosilica and DDS. The curing temperature were increased with increasing wt. % of nanosilica. Thermal studies were done using thermal gravimetric analyzer. Rheometric thermal analyser having TG1500 module was used for recording TG/DTG traces. These cured epoxy nanosamples have shown the significant improvement in the thermal properties.